Public knowledge, attitudes and practices related to antibiotic use and resistance in Singapore: a cross-sectional population survey - Li Yang Hsu; Alex R Cook; Clarence C Tam; Jane M Lim; Minh Cam Duong (BMJ Open, 2021)
Objectives The WHO’s Global Action Plan on Antimicrobial Resistance (AMR) includes increasing overall public awareness of appropriate antibiotic use and resistance as a key priority area. We aimed to measure public knowledge, attitudes and practices of antibiotics and antibiotic resistance in Singapore, as well as their healthcare-seeking behaviours relating to respiratory illnesses, providing baseline data against which to measure the progress of future interventions.Design A cross-sectional study.Setting The general population in Singapore.Participants Between May and June 2019, we conducted a survey via an online panel in Singapore with 706 respondents.Results Our findings indicated common misconceptions surrounding antibiotic effectiveness and mechanisms of antibiotic resistance—most participants thought that resistance occurs when our bodies become resistant to antibiotics (62.5%) or when antibiotics become less powerful (48.5%). In multivariable analyses, better knowledge scores were associated with more favourable antibiotic attitudes (β=0.29; 95% CI 0.20 to 0.37). In addition, more favourable attitude scores were associated with lower odds of both expecting (OR: 0.84, 95% CI 0.72 to 0.99) and being prescribed antibiotics by a primary care doctor (OR: 0.76, 95% CI 0.63 to 0.90).Conclusions This study presents important information about population perceptions towards antibiotics and antibiotic resistance in Singapore. Results from this study emphasise the importance of effective public communication strategies to promote responsible antibiotic use locally and should be used to inform future implementation of programmes and activities as laid out in Singapore’s National Strategic Action Plan on AMR.